Engineering of a Potent Recombinant Lectin-Toxin Fusion Protein to Eliminate Human Pluripotent Stem Cells - Hiroaki Tateno; Fumi Minoshima; Sayoko Saito (Molecules, 2017)
The use of human pluripotent stem cells (hPSCs) such as human embryonic stem cells (hESCs) and human induced pluripotent stem cells (hiPSCs) in regenerative medicine is hindered by their tumorigenic potential. Previously, we developed a recombinant lectin-toxin fusion protein of the hPSC-specific lectin rBC2LCN, which has a 23 kDa catalytic domain (domain III) of Pseudomonas aeruginosa exotoxin A (rBC2LCN-PE23). This fusion protein could selectively eliminate hPSCs following its addition to the cell culture medium. Here we conjugated rBC2LCN lectin with a 38 kDa domain of exotoxin A containing domains Ib and II in addition to domain III (PE38). The developed rBC2LCN-PE38 fusion protein could eliminate 50% of 201B7 hPSCs at a concentration of 0.003 μg/mL (24 h incubation), representing an approximately 556-fold higher activity than rBC2LCN-PE23. Little or no effect on human fibroblasts, human mesenchymal stem cells, and hiPSC-derived hepatocytes was observed at concentrations lower than 1 μg/mL. Finally, we demonstrate that rBC2LCN-PE38 selectively eliminates hiPSCs from a mixed culture of hiPSCs and hiPSC-derived hepatocytes. Since rBC2LCN-PE38 can be prepared from soluble fractions of E. coli culture at a yield of 9 mg/L, rBC2LCN-PE38 represents a practical reagent to remove human pluripotent stem cells residing in cultured cells destined for transplantation.